A global meta-analysis of soil respiration and its components in response to phosphorus addition. (August 2019) - Feng, Jiguang; Zhu, Biao
Abstract: Increasing phosphorus (P) deposition induced by anthropogenic activities has increased the availability of P, and thus could affect ecosystem carbon cycling. Although soil respiration ( R s ) plays a crucial role in driving the global carbon cycle and regulating climate warming, a general pattern reflecting the R s response to P addition in terrestrial ecosystems remains unclear. Here, we conducted a meta-analysis from 102 publications to explore the generalities and mechanisms of responses of R s and its components to P addition across various ecosystems at the global scale. Our results showed that P addition did not significantly change R s and heterotrophic respiration ( R h ) across all ecosystems, but this P addition effect varied among ecosystem types ( p < 0.05). Specifically, P addition significantly increased R s by 17.4% in tropical forest and by 31.7% in cropland, depressed R s by 13.7% in wetland ( p < 0.05), and had minor effect in other ecosystems (grassland, boreal forest, and temperate forest). In contrast, P addition did not have significant effect on R h within any specific ecosystem type. Among multiple environmental and experimental variables, mean annual temperature might be the fundamental driver indirectly controlling the response of R s to P addition at the large scale. In addition, P addition increased soil P availability, and changed ecosystem carbon pools and fluxes. The responses of R s and R h were significantly positively correlated with those of soil organic carbon, microbial biomass carbon and belowground biomass, respectively, suggesting that changes of these carbon pools may drive the responses of R s and R h to P addition. Collectively, our findings imply that R s in tropical forests would strongly respond to P enrichment where current soil P availability is low and future P deposition rate is high, provide a framework for understanding R s dynamics under global P deposition, and highlight the need for further field studies partitioning the two components of R s . Graphical abstract: Image 1 Highlights: The responses of soil respiration ( R s ) to P addition decreased with initial soil P availability. P addition increased R s in tropical forest and cropland, but depressed R s in wetland. P addition had minor effects on R h within any specific ecosystem type. Responses of R s and R h to P addition were positively correlated with those of SOC, microbial biomass C and root biomass. R s in tropical forests might strongly respond to future P deposition.